Eastern filbert blight resistant Corylus avellana identified from 20 years of germplasm introduction and evaluation at Rutgers University, New Jersey, USA - Jacobs, Daniel C.; Revord, Ronald S.; Capik, John M.; Molnar, Thomas J. (Frontiers in Plant Science, 2024)
The stem canker disease eastern filbert blight (EFB), caused by Anisogramma anomala, is a major impediment of European hazelnut (Corylus avellana) production in the United States. While most European hazelnut cultivars are highly susceptible to the pathogen, which remains confined to North America, EFB resistant and tolerant genotypes occur in the gene pool at low frequency. At Rutgers University, New Brunswick, NJ, USA, 5,226 trees were grown from open pollinated seeds collected from Russia, Crimea, Poland, Turkey, Estonia, Latvia, Lithuania, Moldova, Azerbaijan, Italy, and the Republic of Georgia between 2002 to 2010. The trees were field planted, exposed to A. anomala under high pathogen pressure, and evaluated for disease response 5-6 years after their establishment. At this point, around four percent were found to be EFB resistant totaling 216 accessions that spanned a wide diversity of seedlots from most countries and regions. However, recent observations show many of these once-resistant selections have since succumbed to EFB. In this study, the long-term disease response of this germplasm was evaluated to identify trees remaining resistant and tolerant and document changes in EFB response over time in relation to their origin. All trees were rated for presence of EFB according to a scale of 0 to 5 where 0 = no EFB and 5 = all stems have cankers. Data were assembled from three sets: first reports from 5-6 years after each planting year, a reassessment in 2017, and a final evaluation in January 2024. Overall, the results showed a significant reduction in resistant individuals from the original reports. By 2017, the population of 216 trees was reduced to 154 and by 2024 it decreased further to 91. Notably, this shift from resistant to susceptible phenotype was severe and abrupt and patterns were observed within related seed lots. These patterns were also apparent in trees where their resistance (R) genes were mapped. Specifically, all selections with R genes mapped to linkage group (LG) 6 now expressed severe EFB, while those with R genes mapped to LG 2 or 7 remained free of disease. These results strongly suggest pathogenic variation present over time played a role in the breakdown of resistance. Fortunately, despite loss of some of the germplasm, a wide variety of trees spanning most collection origins still remain free of EFB. These 91 trees from 56 distinct seedlots originating from 7 countries are formally documented in this manuscript to facilitate their long-term preservation, continued evaluation and sharing, and to increase global awareness of this valuable genetic resource for future research and breeding.